Efeitos do ruído em funcionários de casas noturnas da cidade de São Paulo - Sousa, Millena Nóbrega Campos de (2009)
Introduction: The electronically amplified music represents an occupational exposure to noise for employees of nightclubs. Such exposure can cause health effects of these workers. Aim: Verifying the effects of noise on hearing and health of employees of nightclubs in the city of Sao Paulo, exposed to electronically amplified music. Method: The sample comprised 50 employees of two nightclubs in the city of Sao Paulo. The procedures were performed: anamnesis, tympanometry and Distortion-Product Otoacoustic Emissions (DPOAE). Results: The most complaints were: tinnitus (18.0%) and intolerance to loud sounds (16.0%), headache (24.0%) and insomnia (22.0%), respectively. Most employees 31(81.6%) reported audiometry within the normal pattern of bilateral normality. The DPOAE test showed absence of responses in the left ear in 21 (42.0%) employees and 17 (34.0%) in the right ear. The absence was bilateral in 22% of the sample (n = 11). The most affected were f2 3174 Hz, 4004 Hz and 6348 Hz. There was a correlation between the results of DPOAE of the right ear with only the variables complained of dizziness and smoking habits. Conclusion: The DPOAE test may be useful for early identification of changes that come in a PAIR employees exposed to electronically amplified music